Penentuan Prioritas Pelayanan Pengguna Jasa Kereta Api Dalam Transportasi Antarmoda Di Stasiun Gambir - Gusleni, Yessi (Warta Penelitian Perhubungan, 2010)
This research study is a continuation of the senrice user qualihJ of railwat; senrice in intennodetransport at the Gambir station, with the result of research using IPA analysis metlwds (ImportancePerformance Analysis) and CSI (Customer Satisfaction Index), there are 7 (seven) attribute that hasvalue perception of low mlue but lurue high expectntions, the ease of obtnining information routejbusroute for the train seruices user inter-1110rfe of transport, sernrity guarantees for railwm; sennce userinter-mode of transport, officer prauide sen1ice to train user wlw have limited (disabled, elderly, etc).T7re crossing facilities, street facilities (corridor/road interface), and facilities for disabled/elderly.This rearch has the objective to determine tire priorities that can be done to improve intermodetransport senTices in Gambir station for train senrice users pracrided bt; PT. Kereta Api (Pesero) andtire local gavernment of D Kl frzknrtn .Result from research of seniice qualih; for train user i11 intermode of transport in Gambir stations,furtl?er in this study, in order to determine tire priority using tire quality function deplot;ment (jfd)analysis metlwd.The result of Quality Fuction Deplot;ment (QFD) analysis can re identified 13 priorities that can reimplemented to imprave the management of senTice quality.